2005
DOI: 10.1007/s11172-005-0444-8
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of spiro derivatives of 2,4-dimethyl-2,3,4,4a,5,6-hexahydro-6H-benzo[c]quinolizine

Abstract: The reactions of 2 (3,5 dimethylpiperidino)benzaldehyde with Meldrum´s acid and cyclo hexane 1,3 dione occur as a tandem of the Knoevenagel condensation and cyclization pro moted by the tert amino effect. The cyclization yields only one isomer with the axial hydrogen atoms in positions 4 and 4a of the benzoquinolizine ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…This proceeded via isomerization of the initial kinetic intermediate. While the barbiturate nucleus is well suited to this process, given our interest in related tetramates both for antibacterial drug discovery and for the generation of novel three-dimensional drug templates, we examined them for their suitability in the T-reaction. Access to spirocyclic tetramates has been rarely reported. In our case, an additional level complexity is added by the chiral nature of the tetramate, as opposed to the nonchiral barbiturate, which converts the spirocenter into yet another quaternary carbon.…”
Section: Introductionmentioning
confidence: 84%
“…This proceeded via isomerization of the initial kinetic intermediate. While the barbiturate nucleus is well suited to this process, given our interest in related tetramates both for antibacterial drug discovery and for the generation of novel three-dimensional drug templates, we examined them for their suitability in the T-reaction. Access to spirocyclic tetramates has been rarely reported. In our case, an additional level complexity is added by the chiral nature of the tetramate, as opposed to the nonchiral barbiturate, which converts the spirocenter into yet another quaternary carbon.…”
Section: Introductionmentioning
confidence: 84%
“…The reaction progress and purity of the products were monitored by thin-layer chromatography on Silufol UV-254 plates with 1:1 and 1:2 ethyl acetate-hexane as the eluent and visualization by UV light or iodine vapor. o-Dialkylaminobenzaldehydes 1a-i were obtained in 60-80% yield by nucleophilic substitution of the fluorine atom in 2-fluorobenzaldehydes with the corresponding cyclic dialkylamines according to our previous procedure [9]. A commercial sample of 2-fluorobenzaldehyde was obtained from Acros.…”
Section: Methodsmentioning
confidence: 99%
“…Knoevenagel condensation products 3a-e,h,i could not be isolated in the condensation of 2-piperidinobenzaldehydes 1a-e,h,i, since the cyclization to give 1,2,3,4-tetrahydroquinolino-5-carbonitriles 4a-e,h,i dominated under these reaction conditions [9]. Knoevenagel condensation products 3f,g, that did not undergo cyclization in toluene, were isolated only in the case of benzaldehydes 1f,g.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…One of the isomers could be isolated with a yield of 33% by fractional crystallization from aqueous alcohol. We also established [39] that the reaction of 2-(3,5-dimethylpiperidino)benzaldehyde (4g) with Meldrum's acid and cyclohexanedione was stereoselective and led to the formation of only one isomer 42b with the axial arrangement of the hydrogen atoms at positions 4 and 4a of the pyrido[1,2-a]quinoline ring, as shown by the spin-spin coupling constant J = 9.7-9.8 Hz in the 1 H NMR spectra of the obtained compounds. It was thus found that the cyclization by tert-amino effect mechanism occurred diastereoselectively when there was a substituent at the β-carbon atom in the dialkylamino group.…”
Section: -97%mentioning
confidence: 99%